(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Greek and Latin are two of the oldest languages in the world, and they have both contributed significantly to the field of medicine. This comparative analysis aims to explore the origins and meanings of Greek-Latin terms commonly used in medicine. The study examines how these languages have influenced the development of medical terminology and how they continue to play an essential role in modern medicine.